HOW INDUCTED IS THE INDUCTED? INDUCTION PROGRAM AND PROFESSIONAL STANDARDS OF PERFORMANCE IN CAPIZ - Almoroto, Rizza Mae; Vasquez, Michael; Dollete, Segundina F (IDEAS: Journal of Management & Technology, 2025)
This study aimed to assess the level of the induction program and the extent of Professional Standards of Performance in Capiz, addressing a gap in literature within the context of Capiz, other school divisions in the region, and the Philippines. The research employed a mixed-method approach using an explanatory sequential design, with 295 participants and eight focus group discussions (FGDs) involving newly hired teachers in the school's division of Capiz. Quantitative data were collected using a researcher-made questionnaire and analyzed using SPSS Statistics version 26, employing various statistical methods. Qualitative data were analyzed using the descriptive phenomenological approach. The findings revealed that the level of the induction program and the Professional Standards of Performance were "very high evident." Furthermore, age and sex were found to significantly influence the level of the induction program, with older beginning teachers demonstrating a higher level of understanding, and female inductees outnumbering males. Regardless of respondents' profiles, there was no statistically significant difference in the extent of Professional Standards of Performance in Capiz. Additionally, the study established a significant relationship between the level of the induction program and the extent of professional standards of performance in the Schools Division of Capiz. The FGD participants encountered various challenges in their professional journey, leading to the emergence of three themes: feeling challenged, being challenged, and becoming a challenger. These findings provide valuable insights into the effectiveness of the induction program and the professional performance standards in Capiz, shedding light on the experiences and perceptions of newly hired teachers in the region. As a result, it is essential to consistently provide strategic mentoring and thorough professional development that aligns with effective practices as it will significantly enhance the induction program and ensure that it meets professional standards of performance.